JAMUR TIRAM PUTIH (Pleurotus ostreatus) SEBAGAI OLAHAN DASAR ISIAN KEBAB - Lalu Amrullah; Marsahip (JURNAL TAMPIASIH, 2022)
Background: Oyster mushroom (Pleurotus ostreatus) is a food ingredient that is widely loved by the public, the nutritional content of oyster mushrooms is quite high, contains nutrients including: protein, fat, phosphorus, iron, thiamin, riboflavin and contains 18 kinds of amino acids which needed by the human body, besides that consuming oyster mushrooms can help lower cholesterol levels, anti-oxidants, accelerate wound healing, repair red blood cells, skin care, and others. Kebab is a fast-food Middle Eastern meal that is quite popular. The purpose of this experiment was to make a formulation of oyster mushroom kebabs by comparing kebabs without liquid milk and with the addition of 35 mL and 70 mL of liquid milk per batter.Methods: The study used an experimental experiment using 3 treatments.Results: The difficulty value in terms of the color of the kebabs made from oyster mushrooms was not attractive enough compared to commercial kebabs made from meat, that the addition of milk to the oyster mushroom mixture did not change the aroma of the mushroom kebabs, according to paneli liquid milk did not add a savory taste to the mushroom burgers. The use of mushrooms as an ingredient in processed kebabs contains lots of vitamins and minerals and is rich in fiber.Conclusion: This study shows that the dough in treatment C has the appearance, color, taste, and soft texture of the resulting kebabs. ABSTRAK Latar Belakang: Jamur tiram (Pleurotus ostreatus) merupakan bahan makanan yang bayak di gandrungi masyarakat, kandungan gizi pada jamur tiram cukup tinggi, memiliki kandungan nutrisi meliputi: protein, lemak, fosfor, zat besi, thiamin, riboflavin dan mengandung 18 macam asam amino yang dibutuhkan tubuh manusia, selain itu mengkonsumsi jamur tiram dapat membantu menurunkan kadar kolesterol, anti oksidan, mempercepat penyembuhan luka, perbaikan sel darah merah, perawatan kulit, dan lain- lainnya. Kebab adalah makan Timur Tengah siap saji yang cukup digemari. Tujuan dari percobaan ini adalah membuat formulasi kebab jamur tiram dengan membandingkan kebab tanpa susu cair dan dengan penambahan susu cair 35 mL dan 70 mL per-adonan.Metode: Penelitian menggunakan percobaan exsprimental menggunakan 3 perlakuan.Hasil: Nilai kesukaran dari segi warna kebab yang terbuat dari jamur tiram belum cukup menarik dibandinglkan dengan kebab komersial yang terbuat dari daging, bahwa penambahan susu pada adonan jamur tiram tidak merubah aroma kebab jamur, menurut panelsi susu cair tidak menambah rasa kegurihan pada burger jamur. Penggunaan jamur sebagai bahan olahan kebab banyak mengandung vitamin dan mineral serta kaya akan searat.Kesimpulan: Penelitian ini menunjukan adonan pada treatment C mempunyai penampilan, warna, kegurihan, dan tekstur yang lembut pada kebab yang dihasilkan.